Parity nonconservation in trinucleon bound states - Kotlyar, V.; Nogga, A. (Вопросы атомной науки и техники, 2007)
Tensor and operator representations for wave function (WF) of three–nucleon bound states are discussed. It is supposed that space parity is not conserved in interaction between nucleons. The WFs of ³He and ³H are expressed in terms of 16 scalar functions, which depend on the magnitudes of the relative momenta and the angle between them. These functions are real in the case when nuclear forces do not violate time reversal symmetry. Characteristic features appropriate to WFs of deuteron and 3N nuclei in operator form (OF) are compared. Досліджуються тензорне та операторне представлення для хвильової функції зв’язаного стану трьох нуклонів. Вважається, що просторова парність не зберігається при взаємодії між нуклонами. Хвильові функції ядер ³He і ³H виражаються через 16 скалярних функцій, які залежать від величин відносних моментів та кута поміж ними. Функції є дійсними, коли ядерні сили інваріантні відносно обернення часу. Проведено порівняння операторних форм для хвильових функцій дейтрона та 3N-ядер. Исследуются тензорное и операторное представления для волновой функции связанного состояния трех нуклонов. Предполагается, что пространственная четность не сохраняется во взаимодействии между нуклонами. Волновые функции ядер ³He и ³H выражены через 16 скалярных функций, которые зависят от величин относительных моментов и угла между ними. Функции вещественныe, когда ядерные силы являются инвариантными относительно обращения времени. Проведено сравнение операторных форм для волновых функций дейтрона и 3N-ядер.